Exploring Local Wisdom Values as an Effort to Maintain Javanese Culture in Elementary Schools - Cusni Anjani; Enok Maryani; Mubiar Agustin; Lutfi Fitri Asylah; Elisabeth Widi Manik (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
Culture in Indonesia has many varieties, one of which is Javanese culture which is rich in strong cultural values. Local culture is a national asset that needs to be seriously observed and cared for. However, local wisdom which is part of the culture is often ignored because it is seen as not in accordance with the times. This is a challenge in preserving local wisdom, especially in schools. So that the alternative solution is to include Javanese local wisdom values as an integral part of subjects or extracurricular activities in elementary schools. On this basis, this research was conducted to see how local wisdom can be integrated in teaching materials and learning activities in elementary schools. Elementary school is a very important level of education in shaping character and providing basic knowledge to students. The purpose of this research is to describe the values of local wisdom from various regions in Java that can be used in primary schools as an effort to preserve local wisdom. The research method used is literature study. With the analysis of this study, it becomes an inspiration or transfer of local wisdom values from teachers to students in elementary schools.